SUBTITLE STRATEGIES IN A MOVIE ENTITLED ENCANTO - Elsa Sandra Eprilia; Gita Rahmi (Jurnal Sosial Humaniora dan Pendidikan, 2022)
This research aims to analyze translation strategies in Indonesian subtitles of a movie entitled Encanto. The research method of this study was a qualitative method and used Gottlieb (1992)'s theory of subtitling strategies. Data for the study were collected from dialogues and Indonesian subtitles in a movie entitled Encanto, such as: expansion, paraphrase, transfer, imitation, transcription, dislocation, condensation, decimation, deletion, and resignation. Based on the analysis, the researcher found 8 out of 10 subtitling strategies from 216 data, with transfer as the most used strategy in the movie entitled Encanto.